Challenges and Supporting Factors in the Management of Guidance and Counseling in Indonesian Secondary Schools - Suci Amelia Mardiah; Neviyarni S; Yarmis Syukur (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The study digs into the challenges, supporting factors, and research trends in guidance and counseling (BK) management in Indonesian secondary schools. Using a Systematic Literature Review (SLR) based on the PRISMA 2020 protocol, the team searched Google Scholar, Portal Garuda, Neliti, and various university repositories for works published from 2010 to 2025. Out of 103 articles, only 14 fit the inclusion criteria. The review exposes structural, technical, and cultural barriers: counselors overloaded with non-BK tasks, inadequate facilities, weak professional supervision, and little support from school policies (Pratiwi, 2012; Rahman, 2019; Abdullah, 2021; Yusuf, 2023). On the positive side, school leadership, counselor training, and inter-party collaboration help the process (Lubis, 2022; Irawan, 2022). Most studies rely on descriptive qualitative methods, but few focus on supervision models, technology, or longitudinal, evidence-based research. This paper calls for stronger guidance counseling management through institutional and policy reforms.